Evaluation and Effect of Carbon Disclosure Quality in China: Based on the Perspective of Investor Protection. Issue 9 (15th July 2021) - Tang, Yongjun; Shen, Yuxin; Yang, Qinglong; Zhao, Zhihui
ABSTRACT: To evaluate the carbon disclosure quality of China's Shenzhen-Shanghai listed companies and its impact on investor protection, this paper constructs an evaluation index framework for carbon disclosure quality. The content analysis and principal component factor analysis methods were used to calculate the index score of the carbon disclosure quality, while empirical research on investor protection indexes was carried out by the method of variance weighting. This study found that an improvement in carbon disclosure quality can effectively protect the interests of investors, especially those of controlling shareholders and minority shareholders, but the degree of protection of large shareholders' interests decreases with the improvement in the quality of carbon disclosure.